2001
DOI: 10.1106/bklq-e2yg-d2la-rg3r
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Radiographic Analysis of Fiber Reinforced Polymer Composites

Abstract: X-ray radiographic examination of the bone fracture healing process is a widely used method in the treatment and management of patients. Medical devices made of metallic alloys reportedly produce considerable artifacts that make the interpretation of radiographs difficult. Fiber reinforced polymer composite materials have been proposed to replace metallic alloys in certain medical devices because of their radiolucency, light weight, and tailorable mechanical properties. The primary objective of this paper is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 7 publications
0
15
0
1
Order By: Relevance
“…22 We suggest that navigational assistance can be helpful in the safe resection of malignant bone tumours and may lead to improved oncological and functional outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…22 We suggest that navigational assistance can be helpful in the safe resection of malignant bone tumours and may lead to improved oncological and functional outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…Radiographic analysis of CFR-PEEK composites confirmed superior radiolucency to other composites, allowing for complete cortical bone visualization [7]. Studies examining metal alloy implants found that titanium produces the least CT artifact, but still results in metallic streak artifact, limiting evaluation of immediate periprosthetic tissues [8,9].…”
Section: Introductionmentioning
confidence: 95%
“…A compressive test was designed according to the American Society for Testing and Materials (ASTM) testing standard D695-02 [6] to determine the elastic modulus. Cylindrical test specimens were machined from stock PEEK-OPTIMA 1 LT1 rod material (Grade LTIR30, Invibio, Lancashire, UK), with dimensions 12.7 mm diameter by 50.8 mm length to fulfil the required slenderness ratio of 11-16.…”
Section: Quasi-static Compressive Testingmentioning
confidence: 99%